Model Pentahelix dan Kalkulasi Harga Pokok Produksi pada Usaha Kecil Pengrajin Endek di Desa Busungbiu Selama Pandemi Covid-19 - ayu rencana saridewi; Luh Risa Denilla Suari (Jurnal Akuntansi Profesi, 2022)
MSMEs are businesses that are the biggest contributor to the Indonesian economy. Therefore, the efforts to improve the quality of MSMEs are necessary, so does the financial management such as calculating the cost of production. In addition, the appropriate collaboration effort, especially during the pandemic is the Pentahelix model, which is a collaboration model. This research uses interview, observation, and documentation methods. Sari Amertha Tenun Ikat is an MSME located in Busungbiu Village and the business has not yet implemented the entire Pentahelix model because there are obstacles faced. In addition, the calculation of the cost of production is immensely simple and does not record according to a certain format.